Contrasting and prioritizing dimensions in ethnic teacher education: A convergent analysis with LDA and fsQCA - Qimeng Wu; Qiyun Wu (PLoS ONE, 2025)
Previous studies have rarely examined ethnic teacher education from a configurational perspective. This study addresses that gap.This study analyzes 250 peer-reviewed articles from CNKI’s PKU/CSSCI journals (2015–2025), identified using ‘ethnic teacher education/education/teachers’ keywords, refined from 2,672 initial records through manual screening.This study employs a mixed-methods approach to investigate ethnic teacher education in China, combining computational text analysis with configurational methods. This study employs ROST Content Mining 6.0 for semantic network analysis and CiteSpace 6.3 for knowledge mapping. The analysis reveals five core conceptual clusters (development, teachers, ethnicity, education, and region) and five research hotspots, with ‘ethnic regions’ emerging as the dominant focus. Through LDA topic modeling, five thematic dimensions were extracted, ranging from the status of ethnic education to cultural integration in teacher training. These qualitative insights were subsequently quantified and analyzed via fsQCA, yielding six distinct optimization pathways. The findings suggest a dual trajectory for future research: while emphasizing geo-cultural specificity in teacher training program design, the study also identifies universal principles applicable across ethnic education contexts. Accordingly, five policy recommendations are proposed, including diversifying development channels, enhancing cultural responsiveness in pedagogy, and facilitating inter-regional knowledge exchange among ethnic communities. This study introduces the novel integration of LDA topic modeling and fsQCA in educational research. While LDA uncovers latent themes and fsQCA examines causal complexity, their combined application enables simultaneous discovery and validation of configurations a previously unexplored approach in ethnic teacher education.These findings make dual contributions: theoretically, by advancing a novel conceptual framework; and practically, by yielding actionable policy implications for ethnic teacher education development.